PEMBELAJARAN MENULIS TEKS NEGOSIASI PADA SISWA MA KELAS X DENGAN MENGGUNAKAN METODE THINK PAIR SHARE (TPS) DENGAN BERBANTUAN MEDIA POSTER - Indri Astuti Nurpauzi; Wikanengsih Wikanengsih; Yeni Rostikawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Learning is a form of interaction between instructors and student which aims to achieve the expected learning. This research is motivated by the lack of interest of students in writing because student find it difficult to put ideas and ideas into the form of writing. This study aims to examine the scenario of negotiating text learning for students of class X MIPA MA exactly 38 Padalarang by using Think Pair and Share methods assisted by poster media, to examine the responses of teachers and MA students of class X to learning to write negotiating text using Think Pair and Share methods assisted by poster media, and to examine the difficulties experienced by MA grade X students in completing writing negotiation texts. The method used in this research is a qualitative descriptive method, the results of this research method are described or described in accordance with the facts in the field, the subject of this method is 34 students of class X MIPA in MA Exactly 38 Padalarang. The result of this study based on the activities of teacher and student are in accordance with the learning scenarios that have been designed. Teacher activities are very good and student activities are very good. The result of teacher and student responses that the reseachers have observed are already in the high category, with the percentage of teacher responses being 62,5% and student responses 50,9%. The ability of student of class X MIPA in writing negotiating texts is quite good with a final score of 84,5 although there are still some student who still have difficulty in writing negotiating texts specifically regarding Indonesian spelling (EBI) and in writing.